Pengaruh Independensi, Pengalaman Audit, Dan Kompetensi Auditor Terhadap Kualitas Audit - Priskila. S Agustin; Yulinartati; Martiana Nina (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
This study aims to determine the effect of independence, audit experience and auditor competence on audit quality at the East Surabaya Public Accounting Firm. The population used in this study are auditors who work in a Public Accounting Firm located in the East Surabaya Region with a total of 22 KAPs. The sample in this study was selected using a purposive sampling technique. There are 15 KAP willing to become respondents. The number of questionnaires distributed in this study were 75 questionnaires with questionnaire data that could be processed as many as 68 questionnaires. The data analysis technique used multiple linear regression analysis.Based on the results of the analysis and discussion, it shows that there is a positive and significant influence between independence, audit experience and auditor competence on audit quality. In addition, the results of the study show that either simultaneously or partially the independent variables, audit experience and auditor competence have a significant effect on audit quality.